Adipokinetic Hormone Receptor Mediates Lipid Mobilization to Regulate Starvation Resistance in the Brown Planthopper, Nilaparvata lugens - Lu, Kai; Zhang, Xinyu; Chen, Xia; Li, Yue; Li, Wenru; Cheng, Yibei; Zhou, Jinming; You, Keke; Zhou, Qiang (Frontiers in Physiology, 2018)
Lipid storage must be efficiently mobilized to sustain the energy demands during processes of exercise or starvation. In insects, adipokinetic hormone (AKH) and brummer lipase are well known regulators of lipid mobilization. We recently demonstrated that brummer-dependent lipolysis regulates starvation resistance in the brown planthopper, Nilaparvata lugens, one of the most destructive rice pests. The present work investigated the roles of AKH signaling system in lipid mobilization during starvation process in N. lugens. NlAKHR is a typical G protein-coupled receptor (GPCR) and possesses highly structure and sequence similarity with other insect AKHRs. Spatial and developmental expression profiles suggested that NlAKH is released from the corpora cardiaca to activate NlAKHR mainly expressed in the fat body. Starvation significantly induced the expression of NlAKH and NlAKHR, indicating a potential role of AKH signaling system in starvation resistance. To reveal the functions of AKH signaling system, double-stranded RNA (dsRNA)-mediated knockdown of NlAKHR and NlAKH peptide injection were performed. As major results, NlAKHR silencing decreased the levels of 1,2-diacylglycerol (DAG) in the hemolymph and increased the triacylglycerol (TAG) levels in the fat body, whereas NlAKH injection led to a critical accumulation of DAG in the hemolymph and a severe reduction of TAG content in the fat body. Knockdown of NlAKHR resulted in prolonged lifespan and high levels of whole body TAG, indicating an inability to mobilize TAG reserves during starvation. Conversely, NlAKH injection reduced the survival and accelerated TAG mobilization during starvation, which further confirms the roles of NlAKH in lipolysis. Moreover, NlAKHR silencing caused obesity in N. lugens, whereas NlAKH injection depleted organismal TAG reserves in vivo and produced a slim phenotype. These results indicate that lipid mobilization is regulated by AKH signaling system, which is essential to adjust body lipid homeostasis and ensure energy supplement during starvation in N. lugens.